Toxicity of sibutramine hydrochloride-adulterated weight loss supplements in rats based on biochemical and organ weight parameters - Suparmi Suparmi; Suryani Yuliyanti; Hesti W. Karyadini; Andi M.R. Syamsudin; Edil Kurniawan Gau (GarVal Editorial Ltda., 2024)
Context: Weight-loss supplements are typically natural or herbal supplements that promote weight loss and enhance health. However, the increase in consumption results in the fraudulent adulteration of conventional pharmaceutical drugs, such as sibutramine hydrochloride (SHCl). Aims: To determine the toxicity of weight loss supplements adulterated with SHCl in rats. Methods: Five samples (J1-J5) of weight loss supplements adulterated with SHCl were collected from an online market. The toxicity of the samples was evaluated using 42 male Wistar rats for 35 days. The rats were divided into seven groups: control, J1, J2, J3, J4, J5, and SHCl. Results: The J1 supplement resulted in the most rapid weight loss in rats compared to the other supplements tested. The kidney and liver weights of rats administered weight loss supplements adulterated with SHCl were greater than those of control rats. J1 indicated the supplement with the highest level of toxicity. The group administered J1 exhibited the highest levels of toxicity across all evaluated parameters. Conclusions: This study confirmed the toxicity of weight loss supplements adulterated with SHCl in rats, contributing to the understanding and treatment of adulterated weight loss supplements. Dietary supplements for weight loss should be thoroughly screened for undeclared sibutramine hydrochloride adulteration to protect public health and strengthen legal provisions.